Unveiling the path to innovation: Exploring the roles of big data analytics management capabilities, strategic agility, and strategic alignment - Zahid Sarwar; Zhi-hong Song; Syed Tauseef Ali; Muhammad Asif Khan; Farman Ali (Journal of Innovation & Knowledge)
Big data are known to improve operational efficiency, competitiveness, and performance. Despite these unprecedented benefits, the understanding of how big data transform organizational processes remains limited. To address this gap, this research empirically investigates how big data analytics management capabilities (BDAMC) influence innovation performance. This study bases its assumptions on the dynamic capability and knowledge-based views. A PLS-SEM analysis of 199 firms reveals that establishing BDAMC is essential for fostering organizations’ innovation performance. This study advances knowledge by demonstrating that BDAMC enhances organizations’ strategic agility, which subsequently boosts innovation performance. Moreover, the empirical findings reveal that developing BDAMC is crucial for achieving strategic alignment, which in turn reinforces innovation performance. These unique findings hold significant practical value for managers and consultants seeking to leverage big data-related systems within organizations.